Prevalence and Risk Factors of Acne Among Adolescents in Kosovska Mitrovica: a Cross-Sectional Study - Milić, Stefan; Janković, Janko (Scripta Medica, 2022)
Background/Aim: Acne can occur in people of all ages, but mostly affects the population at puberty. Given the high prevalence and large impact that acne has on young people, the aim of this study was to assess adolescents' knowledge about factors that improve or worsen the clinical picture of acne, as well as to evaluate the sources used to obtain information on acne.Methods: This cross-sectional study was conducted on a sample of 460 high school pupils from the Medical School and Gymnasium in Kosovska Mitrovica. A self-administrated questionnaire was used. Univariate and multivariate logistic regressions were used to model the association between gender (males/females) or presence of acne (no/yes) and potential exacerbating and ameliorating factors, as well as sources of information. Results: 36.7 % of the respondents were male and 63.3 % were female. 48.9 % of high school pupils confirmed that they had acne. The main factors that worsen the condition of acne, were irregular face washing (88.7 %), hormones (87.0 %), fatty foods (80.9 %) and sweets (79.3 %). The majority of respondents believed that the intake of more water (83.9 %), cosmetic treatment (77.8 %), dietary changes (75.9 %), holiday (54.1 %) and sunbathing (39.3 %) affect improving acne. Taking more water (OR = 1.77; 95 % CI = 1.01-3.11) as a factor in improving acne was significantly more common in girls, while boys more often believed that sunbathing (OR = 0.62; 95 % CI = 0.41-0.94) and weight loss (OR = 0.53; 95 % CI = 0.32-0.88) affect the improvement of acne. The most important sources of information about acne were the Internet (73.0 %) followed by parents (62.6 %), friends (54.1 %), and a doctor (42.8 %).Conclusion: Acne was more common in women and those with a positive family history. The presence of misconceptions among young people regarding the factors that improve or worsen the condition of acne indicates the need for additional education.
Keywords: Acne vulgaris; Prevalence; Risk factors; Adolescent; Serbia